Optimizing cardiorespiratory fitness after bariatric surgery: highly effective with very low adherence: HIT BAR randomized controlled trial - Finze, Alida; Duddek, Megan; Hetjens, Svetlana; Ghanad, Erfan; Reißfelder, Christoph; Otto, Mirko; Betzler, Johanna; Joisten, Christine; Blank, Susanne (BMC sports science, medicine & rehabilitation, 2025)
Cardiovascular disease and obesity-related comorbidities are key factors addressed by metabolic-bariatric surgery (MBS). Although High intensity interval training (HIIT) has been proven effective in healthy cohorts, limited evidence exists regarding HIIT and adherence towards HIIT after MBS. This study aims to test feasibility and cardiorespiratory effect of HIIT after MBS.
Gesehen am 29.10.2025